Reported eating ability of young children with cerebral palsy: Is there an association with gross motor function? - Weir, K.; Bell, K.; Caristo, F.; Ware, R.; Davies, P.; Fahey, M.; Rawicki, B.; Boyd, Roslyn (2013)
Objective: To examine the association between parent-reported ability of young children with cerebral palsy (CP) to eat different food textures and gross motor functional abilities. Design: Prospective, longitudinal, representative cohort study. Setting: Community and tertiary pediatric hospital settings. Participants: Children (N=170; 110 boys [65%]) were assessed on 396 occasions (range, 1-4 occasions), including 67 at 1 year 6 months (49 boys), 99 at 2 years (66 boys), 111 at 2 years 6 months (71 boys), and 119 at 3 years (64 boys). Interventions: Not applicable Main Outcome Measures: Gross motor function was determined using the Gross Motor Function Classification System (GMFCS). Parent-reported eating ability was determined using 4 items of the Pediatric Evaluation of Disability Inventory. The association between capability to eat food textures and GMFCS level was examined using generalized estimating equations. Results: The distribution of GMFCS levels at initial presentation was as follows: I, n=62; II, n=32; III, n=24; IV, n=22; and V, n=30. Reported capability to eat cut-up/chunky and "all textures" of table foods decreased significantly as GMFCS level increased. A decreased capability to eat pureed/blended and ground/lumpy foods compared with GMFCS I was significantly associated with GMFCS levels IV and V only. Conclusions: Reported attainment of eating skills was closely associated with GMFCS level in young children with CP across age levels. These results emphasize the need for early oral-motor and feeding screening in young children with CP across gross motor functional abilities. © 2013 American Congress of Rehabilitation Medicine.